2015
DOI: 10.1246/cl.150796
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation and Characterization of Polystyrene/Triphenyl Phosphate Nanocomposite via Suspension Polymerization

Abstract: In this work, polystyrene (PS)/triphenyl phosphate (TPP) nanocomposites were prepared by suspension polymerization. The TPP dissolved firstly in styrene monomer, and then suspension polymerization was carried out. The results showed that TPP nanoparticles, being about 50 nm spheres, were homogeneously and uniformly dispersed in a PS matrix, which was first reported. Furthermore, the formation mechanism of TPP nanoparticles was simulated by the dissipative particle dynamics (DPD) method. The flame retardance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our previous research showed that TPP particles were all nanosized spheres, which were shown in Fig. 1, and were dispersed homogenously in the PS matrix [21].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous research showed that TPP particles were all nanosized spheres, which were shown in Fig. 1, and were dispersed homogenously in the PS matrix [21].…”
Section: Resultsmentioning
confidence: 89%
“…In our previous research [21], PS/TPP nanocomposites are prepared successfully by suspension polymerization in one step, and the TPP particles were all nanosized spheres, and dispersed homogenously in the PS matrix. However, it was necessary to study further the formation mechanism of TPP nanoparticles in the PS matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The above results show that HPCTP was dissolved in St monomer at a molecular level, and dispersed nanoparticles were formed during the polymerization process. The PS/HPCTP nanocomposite beads are more conducive to improving the flame retardancy of PS …”
Section: Resultsmentioning
confidence: 99%